A Comparative Study of Euphemism in English and Buginese: Pragmatic Stylistics Contexts - Bachriani Bachriani; Abdul Hakim Yassi; Fathu Rahman (ELS Journal on Interdisciplinary Studies in Humanities, 2018)
The research explores the euphemism in English and Buginese. The difference of one language with other languages can be seen from the aspect of using a euphemism. Likewise, what happens to the differences and similarities of the two languages.This research attempts to describe the form and function of euphemism in English and Buginese Descriptive qualitative method is used to reveal the form and function of euphemism by comparative study to find out the similarities and differences of euphemism in English and Buginese. There are 16 forms of euphemism in English based on Allan and Burridge’s theory. While in Buginese there are 18 form of euphemism, According to this theory, there are 3 main points of the function of euphemism in English while the function of euphemism in Buginese consists of 6 main points. This research shown that euphemism form and function of euphemism in Buginese more complex than euphemism form and fuction in English.